Penggunaan Bahan Herbal Sebagai Disclosing Agent pada Gigi Anak : Scoping Review - Sutanto, Kendy; Widhiyaningsih, Dhyani; Ratna Laksmiastuti, Sri (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: The use of herbal-based disclosing agents that are safe for the body can serve as an alternative disclosing agent to assist the general public in detecting plaque, thereby improving oral hygiene practices during tooth brushing. Objectives: Identify which herbal materials can be used as disclosing agents for children's teeth. Methods: The research was conducted using a PRISMA diagram with databases such as PubMed, EBSCO, and SCOPUS, searching for terms (disclosing solution OR disclosing agent OR disclosure AND natural ingredients OR herbal ingredients AND dental plaque AND children OR child AND dental use). Results: The initial search yielded 340 manuscripts. After removing duplicates and thoroughly screening journals for eligibility, 114 manuscripts were obtained, from which 23 manuscripts met the inclusion criteria for this study. Conclusion: The use of herbal-based disclosing agents is not yet as effective as chemical-based disclosing agents; however, among all the herbal materials studied as disclosing agents, beetroot has proven to be the most effective in identifying plaque surfaces on teeth.